ANALISIS YURIDIS TERHADAP PRAKTIK FINTECH DALAM RISIKO PERJANJIAN PINJAM MEMINJAM ONLINE PADA KREDIT PINTAR - Lubis, Atqiya Annazfi; Sembiring, Idha Aprilyana; Chairi, Zulfi (Fakultas Hukum Universitas Sriwijaya, 2025)
One of the technological innovations in the financial services sector in the industrial revolution 4.0 that is currently in demand is information technology-based money lending services or known as Fintech P2PL on the Smart Credit application. Various advantages are available on this platform, but in reality Kredit Pintar has become a polemic because of the low financial literacy and transparency in the public related to risks in online loan agreements that can cause illegal acts against the rights of service users. The problem in this study is how the validity of online money borrowing agreements on the Smart Credit application, how the responsibility of P2PL Fintech operators for user rights in the risk of online money borrowing agreements, and how to protect the debtor's legal protection in online money lending agreements on the Smart Credit application. The method used in this study is normative juridical with a legislative approach. The data sources used consist of primary, secondary, and tertiary legal materials. Data collection techniques and tools are literature studies and data analysis using descriptive techniques. The validity of the online loan agreement on the Kredit Pintar application has met the legal requirements of the agreement in Articles 1320 to 1338 of the Civil Code so that a legal relationship arises to carry out the rights and obligations for the parties. However, in the practice of Fintech P2PL on the Kredit Pintar application, there is no obligation to provide a form of responsibility for mistakes made by one of the parties in entering into an agreement. Legal protection for debtors on the Smart Credit application can be carried out in a preventive and repressive manner as regulated in Article 29 of POJK Number 77/POJK.01/2016 concerning Information Technology-Based Money Lending Services, namely, transparency in information disclosure by mitigating risks to users and service providers, fair behavior, reliability, confidentiality and data security. Meanwhile, repressive protection based on Article 38 of POJK Number 1/POJK.07/2013 concerning Consumer Protection in the Financial Services Sector, the organizer is obliged to offer compensation or repair of the product or service, if the complaint of the service user proves to be a disadvantaged party.